The spectrum behaviors of light waves on scattering from PT-symmetric semi-soft boundary medium - Xiao, Yingying; Wang, Tao; Liu, Chang (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
The spectrum behaviors of light waves on scattering from a novel kind of medium, i.e., the PT-symmetric semi-soft boundary medium, were discussed, and the dependence of the presentation of the far-zone scattered spectrum on the characteristics of the scattering medium was investigated. The results show that spectral shifts and spectral switches can be discovered in the scattered field, and the direction of spectral switch is closely related to the non-Hermitian parameter, the boundary characteristic, and the effective width of the scattering medium. These results will further enrich the scattering theory and may have some applications in the reconstruction of the structural information of scattering medium.
Optica Applicata, Vol. 54, 2024, nr 4, s. 511-522
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; spectrum; PT-symmetric medium; light waves scattering